FUTHER IMPROVEMENT OF THE INFORMATION CULTURE OF A TEACHER IN THE PROCESS OF PROFESSIONAL ACTIVITY - Saydazimova D.X. (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Information culture is a concept that is often found in specialized pedagogical literature. Most often it is used in relation to students. For them, information culture or media culture implies fundamental (basic) knowledge and skills in the field of information search and semantic processing, which ensure effective information activity. Without this knowledge and skills, successful educational and professional activity is fundamentally impossible, it is the key to information security.